1968
DOI: 10.1002/bip.1968.360061211
|View full text |Cite
|
Sign up to set email alerts
|

Far‐infrared spectra of polyalanines with α‐helical and β‐form structures

Abstract: SynopsisFar-infrared spectra of poly-palanines having the a-helical conformation and the ,%form structure were measured. The spectra of glycine-L-alanine copolymer, silk fibroin, and copoly-D,calanines with different D : L compositions were also measured. In addition to the bands so far reported, four bands at 190, 167, 120, and 90 cm-1 were found for the a-helix conformation and the two bands at 442 and 247 cm-1 were found for the 6 form. The 442 cm-l band consists of the parallel 432 cm-l and perpendicular 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…However, for B. mori silk, in addition to the dominant 243 cm1 absorption band, three other peaks at 335, 427, and 546 cm1 can be discerned, especially for heat-treated samples with reduced water content. Four bands have been previously observed in a similar spectral vicinity at 250, 328, 427, and 553 cm1, respectively, for β-sheet rich fibroin films [39]. In contrast, A. pernyi silk fibers have far-IR absorbance spectra with two discernible peaks—at 229 and 439 cm1.…”
Section: Resultssupporting
confidence: 56%
“…However, for B. mori silk, in addition to the dominant 243 cm1 absorption band, three other peaks at 335, 427, and 546 cm1 can be discerned, especially for heat-treated samples with reduced water content. Four bands have been previously observed in a similar spectral vicinity at 250, 328, 427, and 553 cm1, respectively, for β-sheet rich fibroin films [39]. In contrast, A. pernyi silk fibers have far-IR absorbance spectra with two discernible peaks—at 229 and 439 cm1.…”
Section: Resultssupporting
confidence: 56%
“…23) In consistent with this view, we showed that the 13C chemical shifts of D-and Lalanine residues in the copolymers are well reproduced by the calculated contour map of 13C chemical shifts of N-acetyl N'-methyl-L-alanine amide as a model of (Ala) utilizing the FPT-INDO method. 7) In contrast, it was difficult to explain the changes of '3C chemical shifts by the concept of the y-effect.…”
supporting
confidence: 79%
“…17 . Our data ( Figure 1 and Table I) confirm these observations, but illustrate the richness of the spectrum and the numerous ir active modes present in this molecule.…”
Section: Discussionmentioning
confidence: 95%